Tren desain arsitektur di indonesia yang mempengaruhi kerentanan bangunan terhadap gempa - Livian Teddy (STEKOM PRESS, 2021)
Indonesia is an earthquake-prone zone country. Many victims of life and material due to the earthquake that occurred in Indonesia. One of them is the result of the collapse of the building. Buildings in Indonesia should be designed to withstand earthquakes. The resistance of buildings to earthquakes is highly dependent on their geometric configuration which is closely related to form and space. With the development of the era, it also affects the architectural 'trend' favored by architects and clients. But without realizing this trend can affect the vulnerability of buildings to earthquakes. Design trends carried out by architects that can affect the vulnerability of buildings to earthquakes are: 1). Architectural styles that are developing in the world, 2). Transformation of the geometric form of the building, 3). Selection of building materials, 4). Placement of swimming pools on the roofs of high-rise buildings, and 5). Use of building modules.